USING MNEMONICS TO IMPROVE VOCABULARY, BOOST MEMORY AND ENHANCE CREATIVITY IN THE ESL CLASSROOM - Nirmala Ramakrishnan Pillai (The English Teacher, 2004)
In line with the aspirations of the National Educational Philosophy and Vision 2020, schools are expected to produce students who are not only proficient in English but are also creative and innovative. However, weak and average ability students in the ESL classroom at both the lower and upper secondary levels have been found to have problems with vocabulary, spelling and pronunciation despite years of learning the same thing. One technique that has been found effective to address the above problems in the ESL classroom is mnemonics. This paper provides information on how visual mnemonics, physical mnemonics and other mnemonic devices can be used in the ESL classroom to improve vocabulary, boost memory and enhance creativity.